Information Sciences and Systems 2014 Proceedings of the 29th International Symposium on Computer and Information Sciences - Czachórski, Tadeusz; Gelenbe, Erol; Lent, Ricardo (Springer International Publishing : Imprint: Springer, 2014)
Based on a rigorous selection of submissions to The 29th International Symposium on Computer and Information Sciences (ISCIS 2014),  this books includes some of the most recent ideas and technical results in computer systems, computer science, and computer-communication networks. It offers the reader a timely access to innovative research and advances in computing and communications from many different areas of the world.  The topics covered include (but are not limited to) computer architectures and digital systems, algorithms, theory, software engineering, data engineering, computational intelligence, system security, computer systems and networks, performance modeling and analysis, distributed and parallel systems, bioinformatics, computer vision and significant applications such as medical informatics and imaging.   The 29th International Symposium on Computer and Information Sciences (ISCIS 2014) took place in Krakow Old City, Poland on October, 27-8, 2014.